Nova Delphini 2013 = Pnv J20233073+2046041 - Waagen, E.; Murawski, G.; Sergey, I.; Hallsten, P.; Corp, L.; Wikander, T.; Sonka, A.; Gazeas, K.; Oksanen, A. (2013)
Selected CCD photometry of the nova forwarded by E. Waagen, AAVSO: Aug. 13.955 UT, [10.2 (G. Murawski, Suwalki, Poland; V-band); 14.817, V = 6.5 (I. Sergey, Molodechno, Belarus); 14.872, V = 6.43 (P. Hallsten, Vasterhaninge, Sweden); 14.876, B = 6.43 (L. Corp, Rodez, France); 14.877, V = 6.11 (Corp); 14.878, R = 5.68 (Corp); 15.837, B = 5.35 (T. Wikander, Borlange, Sweden); 15.883, V = 5.13 (A. Sonka, Bucharest, Romania); 16.037, I = 4.60 (K. Gazeas, Athens, Greece); 16.035, R = 4.71 (Gazeas); 16.033, V = 4.80 (Gazeas); 16.031, B = 4.97 (Gazeas); 16.279, V = 4.44 (A. Oksanen, Muurame, Finland); 16.278, B = 4.82 (Oksanen);